Implantación contable mediante el sistema de cuenta múltiple en la farmacia San Isidro de la ciudad de Loja, periodo del 01 de enero al 31 de abril del 2014 - Silva Bravo, Myrian Ximena (2015)
This so-called investigative work "IMPLEMENTATION ACCOUNTING OFFICER BY THE SYSTEM FEATURES MULTIPLE PHARMACY SAN ISIDRO CITY OF LOJA, PERIOD FROM 01 JANUARY TO 31 APRIL 2014", justifies itself providing theoretical and practical elements on the proper management of the accounting records allowing to interpret the various commercial activities that allow the owner to know each of accounting movements daily running of the company. In the present work met the objectives raised that led us to the implementation of the accounting of the pharmacy from the initial inventory that allowed us to know values, goods, services and real obligations in which was the company also devised a plan and manual of accounts that served as support for the proper realization of the accounting process that resulted in the issuance of financial statements allowing the owner to make better financial organization. Also bank reconciliations were performed and it was Assistant purchasing, sales, customers, suppliers, develop payment roles and liquidations of VAT which allowed us to optimize the information in the accounting records, to finally make the ending inventory giving to know relevant information about the business owner. Among the key findings is evidence that the company does not have proper control of the transactions that occur on a daily basis, recommending taking corrective measures and developing financial statements Royal for a successful progress and improvement of the pharmacy.